Animated Video-Based Learning Media on Science and Social Content on the Water Cycle Topic for Fourth Grade of Elementary Schools - Natalia, Ni Kadek Dwipiyani; Bayu, Gede Wira; Trisna, Gusti Ayu Sukma (Thinking Skills and Creativity Journal, 2024)
There is a lack of use of learning media in the learning process and the learning process is always teacher-centered. This makes it difficult for students to understand the material delivered so that the classroom atmosphere becomes passive. The purpose of the research is to develop a valid and practical animated video-based learning media on the topic of water cycle in grade IV elementary school. The researcher uses the ADDIE model in developing this media with steps including analysis, design, development, implementation and evaluation. This study takes the subject of material experts, media experts, practitioners and student responses, in this study using qualitative and quantitative descriptive analysis methods. The average results of the validity of animated videos from material experts were 95.5% very good, from media experts 92% were very good, from practitioners 98% were very good and from student responses 96.9 were very good. The learning media based on the animated video on the topic of the water cycle was declared to have passed the validity test and is suitable for use in teaching and learning activities for grade IV elementary school students. The implication of this study is that the use of valid and practical animated video-based learning media can improve student understanding, create a more active and interactive learning atmosphere, and shift the learning approach from teacher-centered to more student-centered.